Workplace Happiness and the Relationship to the Work Motivation among Primary School Teachers in Pasir Gudang District/ Kebahagiaan di Tempat Kerja dan Hubungannya terhadap Motivasi Kerja Guru Sekolah Rendah di Daerah Pasir Gudang (Sains Humanika, 2020)
Happiness is an element capable of motivating the daily routine of individuals, creating self-awareness, creativity and creating harmonious social relationships. Happiness at work is the key to creating positive thinking in the workforce. However, the importance of happiness at work at school is still being a discussion in Malaysia. This study examines the relationship between happiness in the workplace and work motivation among primary school teachers in Pasir Gudang, Johor. This study involved 420 primary school teachers from 20 schools as a sample of the study. This study was conducted using a questionnaire, which identified the level of teachers' happiness and the motivation of teachers in the workplace. The results of Spearman analysis of correlation show high levels of happiness in the workplace and teachers' work motivation. This study supports previous studies showing a positive relationship between happiness in the workplace and teacher work motivation.
Keywords: Workplace happiness; teacher motivation; subjective well-being; career satisfaction; work engagement